A ubiquitous disordered protein interaction module orchestrates transcription elongation - Cermakova, Katerina; Demeulemeester, Jonas; Lux, Vanda; Nedomova, Monika; Goldman, Seth R; Smith, Eric A; Srb, Pavel; Hexnerova, Rozalie; Fabry, Milan; Madlikova, Marcela; Horejsi, Magdalena; De Rijck, Jan; et al. (Science (New York, N.Y.), 2021)
During eukaryotic transcription elongation, RNA polymerase II (RNAP2) is regulated by a chorus of factors. Here, we identified a common binary interaction module consisting of TFIIS N-terminal domains (TNDs) and natively unstructured TND-interacting motifs (TIMs). This module was conserved among the elongation machinery and linked complexes including transcription factor TFIIS, Mediator, super elongation complex, elongin, IWS1, SPT6, PP1-PNUTS phosphatase, H3K36me3 readers, and other factors. Using nuclear magnetic resonance, live-cell microscopy, and mass spectrometry, we revealed the structural basis for these interactions and found that TND-TIM sequences were necessary and sufficient to induce strong and specific colocalization in the crowded nuclear environment. Disruption of a single TIM in IWS1 induced robust changes in gene expression and RNAP2 elongation dynamics, which underscores the functional importance of TND-TIM surfaces for transcription elongation.
Keywords: Transcription Elongation, Genetic; Models, Molecular; Intrinsically Disordered Proteins; proteiny vázající RNA; RNA Polymerase II; exprese genu; DNA-Binding Proteins; Humans; Gene Expression; DNA vazebné proteiny; elongace genetické transkripce; Transcription Factors; Protein Binding; Transcriptional Elongation Factors; mutace; adaptorové proteiny signální transdukční; lidé; proteinové domény; Adaptor Proteins, Signal Transducing; molekulární modely; vnitřně neuspořádané proteiny; RNA-polymerasa II; Protein Interaction Domains and Motifs; mapy interakcí proteinů; vazba proteinů; transkripční elongační faktory; Protein Domains; nádorové buněčné linie; transkripční faktory; Cell Line, Tumor; Mutation; interakční proteinové domény a motivy; RNA-Binding Proteins; Protein Interaction Maps